Monitoring Pathophysiology in the Injured Brain - Eric P. Thelin; David W. Nelson; Adel Helmy; Niklas Marklund (Frontiers Media SA, 2018)
Pathophysiological processes in brain-injured patients can be assessed with an array of methods, with a goal to identify potentially deleterious events, guide treatments and avoid further deterioration. This eBook provides an in-depth exploration into different aspects of neuro-critical care monitoring and how new tools and strategies may be utilized to improve patient outcomes.
English
Keywords: treatment strategies; microdialysis; neuroinflammation; neuro-critical care; subarachnoid hemorrhage; biomarkers; traumatic brain injury; clinical monitoring; multimodality monitoring; neuroimaging